2018
DOI: 10.1111/cea.13174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the basophil activation test and skin prick testing for the diagnosis of sesame food allergy

Abstract: While prospective cohort validation is necessary, joint utilization of BAT and SPT with HPSE extract may obviate the need for OFC in most SFA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
56
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 34 publications
(79 reference statements)
1
56
0
2
Order By: Relevance
“…The interesting conclusions which the authors addressed would suggest the concurrent use of a BAT and SPT for sesame allergy but the authors showed that the CD123 pos /HLADR neg BAT protocol was able to diagnose almost 67% of sesame allergic patients, a range very close to the one obtained with HPSE‐SPT (≥13 mm), that is, 72%, as reported …”
mentioning
confidence: 76%
See 2 more Smart Citations
“…The interesting conclusions which the authors addressed would suggest the concurrent use of a BAT and SPT for sesame allergy but the authors showed that the CD123 pos /HLADR neg BAT protocol was able to diagnose almost 67% of sesame allergic patients, a range very close to the one obtained with HPSE‐SPT (≥13 mm), that is, 72%, as reported …”
mentioning
confidence: 76%
“…While we have stressed the evidence that CD123 does not change its membrane expression upon basophil activation, contrarily to CD203c, which sometimes is used as a phenotyping marker, the ability to evaluate the analytical performance of a BAT may closely depend on the gating strategy actually adopted. If a BAT performance is probably biased by (1) mismatching baso‐related events with further cells expressing the same markers in the gate; (2) loss of fluorescence signal for a defined marker in the gate; (3) problems related to the fluorochrome affinity binding or when the major bias comes from a poorly suited phenotyping strategy, the BAT capability to properly diagnose food allergy might be substantially reduced, so needing the contribution of a SPT …”
mentioning
confidence: 98%
See 1 more Smart Citation
“…To the Editor, In response to the comments of Chirumbolo et al 1 concerning our recent paper, 2 we note that this group has published comments with similar concerns, in reply to various papers over the past several years. [3][4][5][6][7][8][9][10] Their general concern is that basophil gating strategies employed for the basophil activation test (BAT) vary between different publications, with potential for non-maximal basophil purity to affect the interpretation of the BAT and thus its overall accuracy.…”
mentioning
confidence: 85%
“…In this issue of the Journal, Appel et al look at the utility of skin prick testing and the basophil activation test (BAT) for diagnosing sesame food allergy. Sesame is one of those foods were our current diagnostics do not seem to perform very well.…”
mentioning
confidence: 99%